Hacia una caracterización del Inglés para Fines Específicos (Turismo) - Varela Méndez, Raquel (Didáctica. Lengua y Literatura, 2007)
Nowadays nobody doubts the importance of English as the lingua franca used in international communication. In addition to the numerous countries where English is the mother tongue, it is also spoken as a second language in other countries belonging to the Commonwealth, and it is studied as a foreign language within school system in almost the whole world. In this context, professionals and academics of any discipline need to learn English in order to obtain information necessary to carry out their jobs and to communicate with colleagues from other countries. This necessity easily explains the blossoming, starting as early as the 1960s (Barber, 1962; Herbert 1965; en Swales, 1988), of the study of Languages for Specific Purposes (LSP), and more specifically, the work of English for Specific Purposes (Dudley y St John, 1998). Within the field of languages for Specific Purposes, English for Business has traditionally been the area studied. However, nowadays it is English for Tourism which is reaching a high level of popularity, due to the economic and social importance that this sector represents in our country. In the present article the main characteristics of this ESP are revised and some methodological trends for teaching it are shown. De nos jours, personne ne peut nier l’importance de l’anglais comme lingua franca dans la communication internationale. L’anglais, langue maternelle de nombreux pays, est également utilise comme deuxième langue dans les pays appartenant au Commonwealth et, dans les systèmes scolaires, cette langue est pratiquement étudiée partout. C’est pourquoi les professionnels et universitaires doivent étudier l’anglais pour accéder à l’information, afin d’avancer dans leur travail et de pouvoir communiquer avec des collègues étrangers. Ce besoin explique le développement, depuis les années 60 (Barber, 1962; Herbert 1965; en Swales, 1988), des recherches sur les langues sur Objectifs Spécifiques (Languages for Specific Purposes o LSP), et plus particulièrement sur l’anglais sur Objectifs Spécifiques (Dudley y St John, 1998). Parmi les langues sur objectifs spécifiques, on s’est particulièrement penché sur l’anglais des affaires. Cependant, actuellement, l’anglais du tourisme est en forte hausse dans notre pays ce qui, naturellement, est du à la répercussion économique et sociale que ce secteur représente. Cet article revoit les caractéristiques principales de cette langue de spécialité et expose certaines lignes méthodologiques pour son enseignement.